Programming for urban food and nutrition security - Frankenberger, Timothy R.; Garrett, James L.; Downen, Jeanne (International Food Policy Research Institute, 2000)
Governments, development agencies, and communities are attempting to improve urban livelihoods and reduce urban poverty and food and nutrition insecurity... Developing more effective urban programs requires considering some key characteristics that affect the livelihoods of the urban poor: (1) Greater dependency on cash income and less reliance on agriculture and natural resources; (2) Low wages from work at insecure jobs; (3) A large number of women working outside the home; (4) Legal obstacles, including insecure land and housing tenure; (5) Inadequate access to safe water, sanitation, and health services; (6) Frequently weak social networks, which often transcend the geographic boundaries of communities. -- from Text